PEMBUATAN SELAI KULIT PISANG - Rahmiati -; Chalis Fajri Hasibuan; Dewi Nur Anggraeni (Universitas Muhammadiyah Sumatera Utara, 2017)
The purpose of this dedication to provide information about the potential of banana peel waste that can be used as a processed product that is new and has a sale value. Making products based on industrial biology that is easy so that students can apply in the home environment can be used as a provision of entrepreneurship science of these students. In this activity the method of implementation of activities includes 2 stages of discussion and training directly making banana peel skin. Socialization materials include: introduction, explanation of nutrition content on banana peel waste, banana peel potency as raw material for making jam, examples of food products made by utilizing banana peel waste. How to make jam banana peel is done by practice together between the presenters with partners. The first session is demonstration by the speaker who followed by a partner who is guided by the speaker. The procedure for making banana peel skin consists of: preparation of raw materials, banana peeling, blend with blender and homogenization and packaging.